1993
DOI: 10.1111/j.1365-2044.1993.tb06852.x
|View full text |Cite
|
Sign up to set email alerts
|

Pacemaker failure during transurethral resection of the prostate

Abstract: SummaryA case is described of the intra-operative failure of an implanted pacemaker during transurethral prostatic resection caused by a diathermy-related increase in capture threshold which coincided with massive haemorrhage from the operative site. Key wordsEquipment; pacemakers, diathermy. Complications; pacemaker failure. Surgery; prostatectomy. Haemorrhage.There are more than 25000 patients in the United Kingdom with an implanted permanent pacemaker [I]. It is likely that this number will steadily increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(11 citation statements)
references
References 7 publications
0
11
0
Order By: Relevance
“…Contemporary TURP uses a monopolar electrocautery system in which the current passes through the patient' s body: from the active electrode, placed on the resectoscope, towards the return plate, normally placed on the patient' s leg. This has several disadvantages such as heating of deeper tissue, nervous or muscle stimulation and possible malfunction of cardiac pace-maker (6). Resectoscopes using bipolar electrocautery offer an alternative with active and return electrode placed on the same axis on the resectoscope using high current locally but with limited negative effects at distance.…”
Section: Original Papermentioning
confidence: 99%
“…Contemporary TURP uses a monopolar electrocautery system in which the current passes through the patient' s body: from the active electrode, placed on the resectoscope, towards the return plate, normally placed on the patient' s leg. This has several disadvantages such as heating of deeper tissue, nervous or muscle stimulation and possible malfunction of cardiac pace-maker (6). Resectoscopes using bipolar electrocautery offer an alternative with active and return electrode placed on the same axis on the resectoscope using high current locally but with limited negative effects at distance.…”
Section: Original Papermentioning
confidence: 99%
“…Twelve had prostates larger than 50 cm 3 cohort of large glands was 73 min (25-120 min) and median dry resection weight was 36 g (20-62 g), giving a median tissue removal rate of 0.49 g/min. We have found that the visualization of endoscopic landmarks such as the capsule, bladder neck and apex are excellent, and although the gap between the double loop was best seen with a 308 lens, the extremes of electrode excursion were better seen using a 128 lens.…”
Section: Bipolar Electrosurgical Clinical Experiencementioning
confidence: 99%
“…Finally, there is the issue of possible malfunction of certain types of pacemaker [3]. Prostate size and vascularity are perceived to be the two most important factors that have impact on the morbidity of monopolar TURP.…”
Section: Introductionmentioning
confidence: 98%
“…In this system, the electricity runs through the person's body, from a positive electrode that is put on the resectoscope, towards the return sheet that is outed on the person's leg. However, several maleffects such as warming of deeper tissue and provocation of nerves and muscles may happen (3). In bipolar system, for the reason of putting the positive and negative electrode on the same axis of resectoscope and applying high local electrical current, accompanied with less negative effects at distance axis (4).…”
Section: Introductionmentioning
confidence: 99%